Двоякопериодическая задача для полых круговых цилиндров - Толмачев, Станислав Трофимович; Юхимович, Дмитрий Леонидович; Бондаревский, Станислав Львович (НТУ "ХПИ", 2010)
Классический метод мультиполей для произвольной двоякопериодической системы сплошных цилиндров обобщен для полых цилиндров. Задача сведена к бесконечной системе алгебраических уравнений относительно моментов мультиполей. Получены расчетные выражения для решения системы уравнений методом редукции. Приведены примеры численной реализации полевой задачи и предложенного аналитического метода.

A classical multifield method for an arbitrary doubly periodic system of solid cylinders is generalized for hollow cylinders. The problem is reduced to an infinite system of algebraic equations in multifield moments. Computational expressions for solving the system of equations by a reduction method are derived. Examples of numerical implementation of the field problem and the introduced analytical method are given.
A doubly periodic problem for hollow circular cylinders
Keywords: метод мультиполей; суммы потенциалов мультиполей; система сплошных цилиндров; doubly periodic problem; circular cylinders; numerical implementation; potential field